SEDIMENT URINE DESCRIPTION IN THE SUFFER Urinary tract infection (UTI) IN RSUD PROF. DR. ALOEI SABOE - Briyan Saputra Ishak (LP2M Universitas Bina Mandiri Gorontalo, 2022)
Urinary Tract Infection (UTI) is an inflammatory response of the urothelial cells lining the urinary tract due to bacterial invasion and is characterized by bacteria, uria and leukosituria. Urinary tract infections that occur in women and men. The aim of the previous study was to determine the description of the results of erythrocyte examination in the urine sediment of patients with urinary tract infections. Macroscopic Urine What is examined is the volume, color, clarity, specific gravity, odor and pH of urine. Measurement of urine volume is useful for interpreting the results of a quantitative or semi-quantitative examination of a substance in urine and for determining abnormalities in the balance of body fluids. The background of the above problems encourages researchers to find out more about the description of Urine Sediment in Patients with Urinary Tract Infection (UTI) at Prof. Dr. Aloei Saboe. Based on the results of the above study, 15 patients with Urinary Tract Infection (UTI) had morning urine samples taken and urine sediment examinations were carried out in the hospital laboratory. Prof. Dr. H. Aloei Saboe. The results of the urine sediment examination were abnormal or there was an increase in the number of erythrocytes and leukocytes in the urine sediment of the 15 patients. From the results of this study it can be concluded that in patients with urinary tract infections (UTIs) it was found that ertrocytes were more dominated. from 0-2/lpb (93%) and leucocytes more than 0-5/lpb (80%) or abnormal.